2011
DOI: 10.1073/pnas.1103946108
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the MID-PIWI lobe of a eukaryotic Argonaute protein

Abstract: Argonaute proteins (AGOs) are essential effectors in RNAmediated gene silencing pathways. They are characterized by a bilobal architecture, in which one lobe contains the N-terminal and PAZ domains and the other contains the MID and PIWI domains. Here, we present the first crystal structure of the MID-PIWI lobe from a eukaryotic AGO, the Neurospora crassa QDE-2 protein.Compared to prokaryotic AGOs, the domain orientation is conserved, indicating a conserved mode of nucleic acid binding. The PIWI domain shows a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
119
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(123 citation statements)
references
References 32 publications
(66 reference statements)
4
119
0
Order By: Relevance
“…A likely explanation for this is the absence of the adjacent PIWI domain, which is known to contribute to the nucleotide-binding pocket in Neurospora crassa QDE-2 MID-PIWI and full-length eukaryotic Argonaute structures (Boland et al 2011;Nakanishi et al 2012;Schirle and MacRae 2012). In fact, Neurospora crassa QDE-2 MID-PIWI domain is required to bind RNA, while the MID domain alone is insufficient (Boland et al 2011). Therefore, we proceeded by positioning the ligands (NMPs) in the MIWI MID structure by docking analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A likely explanation for this is the absence of the adjacent PIWI domain, which is known to contribute to the nucleotide-binding pocket in Neurospora crassa QDE-2 MID-PIWI and full-length eukaryotic Argonaute structures (Boland et al 2011;Nakanishi et al 2012;Schirle and MacRae 2012). In fact, Neurospora crassa QDE-2 MID-PIWI domain is required to bind RNA, while the MID domain alone is insufficient (Boland et al 2011). Therefore, we proceeded by positioning the ligands (NMPs) in the MIWI MID structure by docking analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Substitution of the tyrosine in Bombyx Siwi with glutamate (Y607E) or extension of the C-terminal end by a single alanine (A) residue (C-term +A), which presumably affects the C terminus's contribution to 5 ′ phosphate recognition within the MID domain (Boland et al 2011;Nakanishi et al 2012;Schirle and MacRae 2012), were found to drastically reduce small RNA binding in vitro (Kawaoka et al 2011). Mutation within the MID domain in AGO clade members is also shown to drastically reduce small RNA binding in vivo (Boland et al 2011;Rudel et al 2011). Taken together, this confirms that 5 ′ phosphate recognition within the Piwi MID domain is essential for piRNA biogenesis in vivo and that the MID environment in some proteins may further specify the 5 ′ -end nucleotide bias of the bound piRNA.…”
Section: Resultsmentioning
confidence: 99%
“…This structural conformation should favor the orientation of the small RNA duplex with the end that is more easily unwound (i.e., the less stable end) toward the phosphate-binding pocket. The high homology of the MID and PIWI domains, in particular the architecture of the C-terminal carboxylate that forms the phosphate-binding pocket, suggests that the binding mode for a small RNA molecule is commonly shared by Ago proteins (Parker et al 2005;Wang et al 2008;Boland et al 2011). In the case of fly Ago2-RISC assembly, Dcr-2/R2D2 binding might double-check or amplify the sensing of thermodynamic asymmetry in addition to Ago2 itself; an siRNA duplex needs to bind Dcr-2/R2D2 before entering Ago2, and yet the duplex might transiently shuttle between Dcr-2/R2D2 and Ago2, with each protein checking the asymmetry, before it is properly docked into Ago2.…”
Section: +Dicer1mentioning
confidence: 99%
“…However, Filipp Frank (Nahum Sonenberg and Bhushan Nagar laboratories, McGill University, Canada) reported that nucleotides and cap analogs readily interact with the hAGO2 MID domain through the miRNAbinding pocket, but that additional nucleotide interactions outside this region were not observed (Frank et al, 2011). Elisa Izaurralde (Max Planck Institute for Developmental Biology, Germany) presented new work on the MID-PIWI lobe of QDE-2 (Boland et al, 2011). Siwi also stably bound longer substrates with 1U preference.…”
Section: Ago Cap-binding and Allosterymentioning
confidence: 99%